Traffic Monitoring via Mobile Device Location. - Martín, Juan; Khatib, Emil Jatib; Lázaro-Legaz, Pedro; Barco-Moreno, Raquel (MDPI, 2019)
Measuring traffic in real time is one of the main functionalities of Smart Cities. To reduce the costs of deployment and operation, traffic measurement with mobile devices has been widely studied. In this paper, a traffic monitoring system using mobile devices is proposed. The proposed algorithm has the advantage of having a very low computational cost, allowing most of the pre-processing to be done in the mobile device and therefore making possible the centralized collection of a massive number of measurements. The proposed system is composed of three algorithms; a map-matching algorithm to correct minor location errors, a Virtual Inductive Loop that estimates the traffic and a traffic data collector that aggregates the information from many devices and combines it with other information sources. The system has been tested in a real scenario, comparing its accuracy with a traditional traffic sensor, showing its accuracy.
Keywords: Global Positioning System; Telecomunicaciones; Traffic monitoring system; GPS; Map-matching; Smartphones; Traffic occupancy; Smart-city